Extranodal NK/T-cell lymphoma, nasal type (ENKTL-NT): An update on epidemiology, clinical presentation, and natural history in North American and European cases - Haverkos, Bradley M. (Curr Hematol Malig Rep, 2016)
Extranodal NK/T-cell lymphoma, nasal type (ENKTL-NT) is an aggressive extranodal non-Hodgkin lymphoma most commonly occurring in East Asia and Latin America but with increasing incidence in the U.S. Data on epidemiology, disease presentation, and outcome for European and North American (“Western”) cases are very limited. We review published landmark clinical studies on ENKTL-NT in the West and report in detail recent data, including our institutional experience. We highlight key observations in its epidemiology, natural history, and trends in clinical management. In the U.S., ENKTL-NT is more common among Asian Pacific Islanders (API) and Hispanics compared to non-Hispanic whites. Published studies indicate less heterogeneity in clinical presentation in Western ENKTL-NT compared to Asian patients. While there is variation in age at diagnosis, presence of antecedent lymphoproliferative disorders, and outcomes among racial/ethnic groups, the universal association of ENKTL-NT with EBV and the poor response of this neoplasm to anthracycline-based therapy are consistent across all geographic areas.